A mercantilização dos bens naturais no setor elétrico: o caso da UHE Barra Grande - Silva, Alexandra Borba da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Electric energy is a commodity of consumption and of production, it is an essential good at current standards of technological and industrial development. It is developed and produced in the capitalist mode of production. Electricity turned a commodity of high profitability, which from is possible to transform the force of work and nature. In Brazil, the main source of electricity is water, which have transformed rivers and created artificial lakes with the purpose of electric energy generation. The hydro-power dam of Barra Grande, build on the Pelotas river, on the Uruguai river basin, is part of the Brazilian electric sector. This power plant flooded an extended area of land, provoked the deforestation of the primary forest of the Mata Atlântica biome, have affected and displaced a great number of people from their lands and homes, which meant an expressive transformation of the space where the dam is built. The purpose of this study is to understand how the concessionary companies of the power plant appropriated natural resources, transforming in commodities for the reason of capital accumulation. The Federal Government is owner of the water resources and responsible for the planing, coordination and regulation of the electric sector, and with laws and rules has benefited companies in the sector. The hydro-power plants are source of high profitability, once they produce energy at a lower cost than thermal electricity...

La electricidad, bien para el consumo y producción, es esencial en el desarrollo tecnológico e industrial de hoy. Desarrollada y producida de acuerdo com el modo de producción capitalista, la electricidad se convirtió en una buena fuente de alta rentabilidad, que es posible a través de la fuerza de trabajo que transforma la naturaleza . En Brasil, la principal fuente de electricidad es el agua, que se estaba convirtiendo los ríos en la secuencia de los lagos artificiales con el propósito de generar electricidad . La presa Barra Grande, construida en el río Pelotas, la Cuenca del Río Uruguay es parte del sector eléctrico brasileño. La planta inundó una gran cantidad de tierra, causó la devastación de los bosques primarios del Bioma Bosque Atlántico, y un sinnúmero de personas desplazadas llegó a tierras y casas, causando una importante transformación en el espacio en el que fue construido. El propósito de este estudio es entender cómo las empresas están apropriándose de los recursos naturales, transformándolos en productos para la acumulación de capital. La Unión, el dueño de los recursos hídricos, es responsable de la planificación, la coordinación y la regulación del sector eléctrico, que actúa con las leyes y normas que se han beneficiado las empresas del sector...

A energia elétrica, bem de consumo e de produção, é essencial nos atuais padrões de desenvolvimento tecnológico e industrial. Desenvolvida e produzida dentro do modo de produção capitalista, a eletricidade se tornou uma mercadoria fonte de alta lucratividade, a qual é possível através da força de trabalho ao transformar a natureza. No Brasil, a fonte principal de eletricidade é a água, o que foi transformando os rios em sequencia de lagos artificiais com o propósito de geração de energia elétrica. A barragem de Barra Grande, construída no Rio Pelotas, Bacia do Rio Uruguai é parte do setor elétrico brasileiro. A usina alagou uma grande quantidade de terra, provocou a devastação de floresta primária do Bioma Mata Atlântica, atingiu e deslocou inúmeras pessoas de terras e casas, provocando uma transformação expressiva no espaço onde foi construída. O propósito desse estudo é compreender como as empresas concessionárias da usina apropriam-se de bens naturais, transformando-os em mercadorias para fins de acumulação de capital. A União, proprietária dos recursos hídricos, é responsável pelo planejamento, coordenação e regulação do setor elétrico, agindo com leis e regras que tem beneficiado as empresas atuantes no setor. As hidrelétricas são fonte de alta lucratividade, uma vez que produzem a energia a um custo de produção menor que a eletricidade produzida de fonte térmica...
Keywords: Geografia; Natureza; Sustentabilidade; Mercadorias; Energia elétrica; Camponeses; Geography